Urban river : rejuvenate the Sungai Kerayong into an ecological corridor in Kuala Lumpur City - Mohd Niza, Wan Nur Zakirah (2018)
The Malaysian urban river corridor faces major physical transformation in the 21st century. The river is rich with ecosystem and bases of life which providing so many functions to the existence of nature and also human systems. However, due to the bad management and public indifference, they are brutally sullied. Rapid development and urbanization have also embroidered and it caused a pollution to occurred, where the governance most does are largely focused on the management of water deficiencies, pollution and floods. Besides that, the impact of rapid growth compounded by competition between the two major industrial sectors, commercial bases and tourism development bordering township and industrialization, has recorded high petition for the use of these spaces. The political situation and the lack of consideration of ecological principles in the design solutions has flickered environmental constraints and inflexible cultures of its landscape character and their ecological system. Therefore, a general approach towards refining the landscape design process and its water quality is essential to protecting the worth of these places. Limited study has been undertaken and more has been created a vital need to discover a better way to improve the design method of the Malaysian landscape urban river corridor development which embraces the needs and objectives of its water quality and multi-ethnic culture without making radical changes to the landscape rivers characters. This paper delivers a brief overview to addressing the important gap and thereby serves to underwrite to the literature review.